The Implications of Law No. 11 2020 Concerning Job Creation on Regional Spatial Planning and Watershed Management - Haris Budiman; Suwari Akhmaddhian; Erga Yuhandra (Faculty of Law, Universitas Pekalongan, 2023)
In 2020, the government issued Law Number 11 of 2020 on Job Creation. This law has received numerous criticisms from the community, especially in the effort to realize self-sufficiency, security, and food sovereignty, as well as to protect agricultural land from the threat of land conversion. The government, on the other hand, claims that a job creation law, often known as omnibuslaw, can simplify and integrate fundamental permits from laws pertaining to location, environmental, and building permits. The problem under study was the implications of Law Number 20 of 2020 concerning Job Creation on spatial planning and watersheds management, employing a normative research method. The results highlight that the aforementioned law has reconstructed law number 26 of 2007 concerning Spatial Planning, which uses digital maps in the determination of RDTR, the integration of spatial planning and zoning plans, as well as the creation of single map policy to overcome land intersection, influencing permits in the regions. In addition, law number 41 of 1999 concerning Forest Area Limits has also been reconstructed, governing the adequacy of forest areas and forest cover in watersheds, which must be maintained at least 30 percent of the area of river basins. The 30% loss of the forest area may result in policy liberalization and the uncontrolled utilization of forest lands for industrial and commercial purposes. At the end, it will exacerbate tensions between spatial planning and watershed management, especially in preserving the adequacy of forest areas and forest cover in watersheds, which is critical to preventing erosion, landslides, and floods, as well as sustaining tree stands, litter, and undergrowth plant.